Renal Extramedullary Hematopoiesis in Mast Cell Leukemia with Bone Marrow Fibrosis - Damian T. Rieke; Laura K. Schmalbrock; Jana Ihlow; Karsten Kleo; Ann-Christin von Brünneck; Florian Nolte; Ulrich Keller; Sebastian Ochsenreither (Case Reports in Hematology)
Systemic mastocytosis is defined by the clonal proliferation of abnormal mast cells. The clinical course can range from indolent forms with normal life expectancy to advanced mast cell leukemia with dismal prognosis. An association with other diseases, including myeloproliferative neoplasia, has been described. We present a case of a 75-year patient with a history of cutaneous mastocytosis who was diagnosed with mast cell leukemia more than 9 years ago and did not receive treatment. The patient presented to our clinic with acute kidney failure because of renal extramedullary hematopoiesis. Bone marrow histopathology revealed extensive fibrosis and 50% infiltration by mast cells with a c-KIT D816V mutation. No mutations supporting primary myelofibrosis were identified. Treatment with midostaurin was started, and the patient was discharged after improvement of renal function. Here, we discuss diagnostic challenges between different forms of mast cell leukemia and overlaps with other hematological malignancies.